Gender-based differences in the relationships among proactive personality, perceived entrepreneurial support and entrepreneurial intention of Chinese private college students: A moderated mediation model - Tian, Jing; Zhang, Mohan; Wu, Yunpeng; Zhou, Haitao (Frontiers in Psychology, 2022)
Although proactive personality has been found to be a key determinant of entrepreneurial intention, few research has explored the mediating and moderating mechanisms underlying this relation. This study intends to investigate the association between proactive personality and entrepreneurial intention, and examines the mediating role of perceived entrepreneurial support and the moderating role of gender. A total of 1515 senior students from Chinese private colleges filled out questionnaires regarding proactive personality, perceived entrepreneurial support, and entrepreneurial intention. Results with SPSS revealed that perceived entrepreneurial support mediated the association between proactive personality and entrepreneurial intention. Moreover, the relationship between proactive personality and perceived entrepreneurial support as well as the relationship between perceived entrepreneurial support and entrepreneurial intention were moderated by gender. Specifically, the positive association between proactive personality and entrepreneurial intention was stronger among male students, and the positive association between perceived entrepreneurial support and entrepreneurial intention was stronger among female students. This study contributes to the understanding of how proactive personality predicts entrepreneurial intention among Chinese private college students, and bears implications for higher education institutions that entrepreneurial education should focus on improving the perceived entrepreneurial support and taking the gender of students into consideration.